Structural genomic abnormalities of chromosomes 9 and 18 in myxopapillary ependymomas - Mahler-Araujo, M. B.; Sanoudou, D.; Tingby, O.; Liu, L.; Coleman, N.; Ichimura, K.; Collins, V. P. (J Neuropathol Exp NeurolJ Neuropathol Exp NeurolJ Neuropathol Exp Neurol, 2003)
Myxopapillary ependymomas (MPEs) are low-grade neuroepithelial tumors typically occurring in the conus-cauda equina-filum terminale region. Limited molecular and cytogenetic analysis of MPEs has not demonstrated consistent abnormalities. In an attempt to clarify the chromosomal status of these tumors and identify commonly aberrant regions in the genome we have combined 3 molecular/cyto/genetic methods to study 17 MPEs. Comparative genomic hybridization of 7/17 tumors identified concurrent gain on chromosomes 9 and 18 as the most frequent finding. The majority of the 17 tumors were also studied using microsatellite analysis with marker spanning the whole chromosomes 9 and 18 and interphase-FISH with centromeric probes for both chromosomes. Our combined results were consistent with concurrent gain in both chromosomes 9 and 18 in 11/17 cases, gain of either chromosome 9 or 18 and imbalance in the other chromosome in 3/17 tumors and allelic imbalances of chromosomes 9 or 18 in 3/17 and 1/17 tumors, respectively. Other abnormalities observed included gain of chromosomes 3, 4, 7, 8, 11, 13, 17q, 20, and X and loss of chromosomes 10 and 22. Our findings represent some steps towards understanding the molecular mechanisms involved in the development of MPE.
Keywords: Adolescent; Adult; Aged; Central Nervous System Neoplasms/genetics/pathology; Chromosomes, Human, Pair 18/chemistry/*genetics; Chromosomes, Human, Pair 9/chemistry/*genetics; Ependymoma/*genetics/pathology; Female; Humans; Male; Microsatellite Repeats/genetics; Middle Aged; Neoplasms, Neuroepithelial/*genetics/pathology; Peripheral Nervous System Neoplasms/genetics/pathology